Demographic Processes of the Nagorno-Karabakh Autonomous Region in the Second Half of the 1920s – in the 1930s - Hovhannisyan, Gayane (History and Culture, 2021)
The purpose of this article is to present demographic processes in the Nagorno-Karabakh Autonomous Region in the second half of the 1920s – in the 1930s. To achieve this goal, we set the following tasks: to explore the main factors that determine the demographic picture of the autonomous region, to present their consequences and impact on demographic processes. During the research process, various methods were used, such as analysis, comparison and juxtapose of various sources, archival documents, press and other materials.Exploring the subject-matter theme, we came to conclusion that the demographic processes of the autonomous region were a consequence of the demographic policy of the Azerbaijani authorities, as well as it was conditioned by the socio-economic and socio-political processes of the Soviet Union. In the second half of the 1920s – in the 1930s, the factors determining the demographic processes in the region are grouped into two parts. The first group of factors is the measures taken by the Azerbaijani authorities. These measures included the reduction of the region's territory due to administrative changes, the formation of Turkic settlements, measures aimed at eliminating nomadic settlements, the resettlement of the Armenian population to other regions for economic ″justifications″, a deliberate slowdown of the socio-economic development of the region. The second group of factors was associated with socio-economic, socio-political processes that engulfed the entire Soviet Union. These include the processes of collectivization, industrialization and repression in the 1930s.
Keywords: demographic processes; industrialization; collectivization; administrative changes; resettlement; emigration; demographic consequences